Correlation Between Emotional intelligence and Learning Achievement in Tarikh Islam lesson Student of Kulliyatu-l Mu’alimat Al-Islamiyah Darussalam Gontor Modern Islamic Institution Second Campus - Zuhrotul Mufidah; Noor Syahid; Samsirin Samsirin (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2020)
Emotional intelligence is a person’s ability to recognize self emotions, manage self emotions, motivate oneself, rocognize other people’s emotions (empathy) and the ability to foster relationships (cooperation) with others. While learning achievement is the result of learning from a learning activity carried out based on measurements and assessments of the results of learning activities in the academic field which are realized in the form of numbers in the report card. According to the results of recent research in the field of psychology prove that IQ is not the only factor that affects one's learning achievement, but there are many other factors that influence one of them is emotional intelligence. If students have high emotional intelligence, it will improve learning achievement. As is well known that learning achievement on Tarikh Islam, especially in class 4th grade KMI in Pondok Modern Darussalam Gontor Putri Campus 2 is still relatively low. From these studies researchers have new ideas to improve learning achievement by studying and increasing emotional intelligence.